2020
DOI: 10.1088/1361-6528/abc8b2
|View full text |Cite
|
Sign up to set email alerts
|

High-performance perovskite photodetectors based on CH3NH3PbBr3 quantum dot/TiO2 heterojunction

Abstract: Organo-lead halide perovskite materials have opened up a great opportunity to develop high performance photodetectors because of their superior optoelectronic properties. The main issue with perovskite-only photodetector is severe carrier recombination. Integration of perovskite with high-conductive materials such as graphene or transition metal sulfides certainly improved the photoresponsivity. However, achieving high overall performance remains a challenge. Here, an improved photodetector is constructed by p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…How to cite this article: S. Ghosh, D. Rana, B. Pradhan, P. Donfack, J. Hofkens, A. Materny, J Raman Spectrosc 2021, 52 (12), 2338. https://doi. org/10.1002/jrs.6141…”
Section: Supporting Informationmentioning
confidence: 99%
See 1 more Smart Citation
“…How to cite this article: S. Ghosh, D. Rana, B. Pradhan, P. Donfack, J. Hofkens, A. Materny, J Raman Spectrosc 2021, 52 (12), 2338. https://doi. org/10.1002/jrs.6141…”
Section: Supporting Informationmentioning
confidence: 99%
“…[1][2][3][4][5][6] Over the past decades the MHPs have emerged as suitable materials for solar cells, light emitting diodes, lasers, transistors, and memory devices. [7][8][9][10][11][12][13] It has been demonstrated that MHP-based photovoltaic devices show power conversion efficiencies of more than 22%, [14,15] and the devices can be produced on cheap non-crystalline substrates by both vapor deposition and solution processing. [8,11,16,17] Their excellent performance originates from the outstanding optoelectronic properties such as direct band-to-band recombination, long exciton diffusion length, high absorption coefficient.…”
Section: Introductionmentioning
confidence: 99%
“…[211] Furthermore, a planar PD with a faster photoresponse of t r /t d = 0.09/0.11 s was developed by engineering the interface between the CH 3 NH 3 PbBr 3 QD and the ALD-TiO 2 ultrathin films. [212] To minimize the degradation of charge separation and collection in photovoltaics, which is induced by the trap-mediated nonradiative recombination related to the trap states in semiconductors, Yan et al [213] fabricated a MAPbI 3 /TiO 2 p-n heterojunction that enables the partial collection of trap-filled charges by a tunneling process. In the trap states, the carriers can be injected into the TiO 2 layer via tunneling and produce an EQE peak around unity and an IQE exceeding 100%, giving rise to near-infrared photovoltaics.…”
Section: Tio 2 /Organometal Lead Halide Perovskitesmentioning
confidence: 99%
“…[ 211 ] Furthermore, a planar PD with a faster photoresponse of t r / t d = 0.09/0.11 s was developed by engineering the interface between the CH 3 NH 3 PbBr 3 QD and the ALD‐TiO 2 ultrathin films. [ 212 ]…”
Section: Heterostructure Photodetectorsmentioning
confidence: 99%
“…The last few years have witnessed the extremely rapid development of organic–inorganic lead halide perovskite (OLHP)-based optoelectronics such as photovoltaics, light-emitting diodes (LEDs), and photodetectors. The power conversion efficiency (PCE) of small-sized perovskite solar cells has rocketed from 3.8 to 22.1% . This rapid progress is attributed to unique optoelectronic properties, in particular, a high absorption coefficient, long carrier lifetime, direct band-to-band transitions, , high photoluminescence quantum yield (PLQY), and long carrier diffusion length .…”
Section: Introductionmentioning
confidence: 99%